BEYOND PLANNING: THE ROLE OF MOTIVATION AND BEHAVIOURAL INTENTION IN TRAVELLERS' DESTINATION DECISION-MAKING — A STRUCTURAL EQUATION MODELLING APPROACH - Babu, S.Ramesh; G.Murugesan (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Travel decision-making is a psychologically complex process influenced by multiple behavioural determinants. This study investigates the factors shaping travellers' destination decisions by extending the Theory of Planned Behaviour (TPB) to incorporate motivation as an additional construct. Data were gathered from 322 domestic travellers visiting Virudhunagar District, Tamil Nadu, using a structured questionnaire measured on a seven-point Likert scale, and analysed through Structural Equation Modelling (SEM). The findings reveal that motivation is the most dominant predictor of both behavioural intention and actual visit behaviour, while behavioural intention strongly mediates the relationship between psychological antecedents and actual visitation. Although attitude and subjective norms did not significantly influence intention, subjective norms exerted a meaningful direct effect on actual visit behaviour, highlighting the persistent role of social influence in travel decisions. Perceived behavioural control demonstrated a significant negative effect on actual visitation, suggesting that perceived constraints inhibit travel activity. The study offers valuable theoretical extensions to TPB and practical insights for destination marketers, tourism planners, and hospitality professionals seeking to enhance traveller engagement and destination competitiveness.